(untitled) - Taylor, Alison (San Francisco, CA, 2002)
This book provides a theoretical framework for the process decisions we make as mediators and then offers specific tools and strategies. Especially beneficial for those without a psychological background, this reference guide explores how mediators' understanding of family dynamics and systems has a direct impact on the effectiveness of our interventions. An excellent guide for the beginning or experienced mediator
Keywords: Family mediation,Family counseling,Dispute resolution (Law),Tư vấn gia đình,Giải quyết tranh chấp (Luật),Hòa giải gia đình